An Analytical Study of Strategies for Teaching Listening Skills According to Dr. Muhammad Saleh Al-Shanati - 'Amaliah, Thariqatul; Baroroh, R Umi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
Listening comprehension is one of the foundational skills in language acquisition, yet its implementation in Arabic language education is often overlooked, especially in many Islamic educational institutions where more focus is placed on grammar and translation. This study aims to analyze the teaching strategies for listening skills (maharah istima’) as conceptualized by Dr. Muhammad Shalih Syanthi in his book Al-Mahārah al-Lughawiyyah. Using a qualitative descriptive method with content analysis, this study examines the pedagogical ideas proposed in the listening chapter of the book. The analysis reveals that Dr. Syanthi emphasizes gradual learning, the use of authentic and contextual audio materials, the development of psychological readiness in learners, active listening exercises, and formative assessment. Moreover, he identifies several key barriers to effective listening—such as distraction, boredom, low stamina, and a critical attitude towards the speaker—and offers practical strategies to overcome them. The findings conclude that M.Syanthi’s framework for teaching maharah istima’ is highly relevant and adaptable for modern Arabic language instruction, especially in enhancing communicative competence and learner-centered pedagogy in both traditional and contemporary settings.